Power of persuasion - Montgomery, Selena (Berkley, 2025)
"Sometimes the power of love . . . A.J. Grayson has come a long way from adopted orphan to fast-rising executive at a cutting-edge technology firm. Now an anti-terrorist agency wants to use the revolutionary artificial intelligence system she developed to thwart a plot against Jafir's monarchy-and handsome, dynamic Damon Toca, the region's newly crowned king. . . . can be the most seductive weapon of all. In six short months, Damon has gone from gallery owner to controversial politician. When his cabinet hires A.J. Grayson-without his consent-he gets ready for a battle. Expecting a computer geek, and skeptical of A.J.'s highly touted secret invention, he is stunned to find a strong-minded beauty who arouses much more than his suspicions. But someone in his inner circle is in league with a treacherous adversary who threatens his throne, his nation's tenuous peace . . . and his future with a woman he'll risk everything to have and to hold"--